Avaliação da qualidade da anticoagulação oral em cardiopatas atendidos em ambulatórios de referência em Belo Horizonte - Rogerio Guimaraes de Lima Silva (2016)
The quality of oral anticoagulation is a critical determinant in the quality of life of patients in continuous use of this class of drugs. Patients with heart disease with indications for oral anticoagulation may benefit from treatment when the time in therapeutic range (TTR) is above 60%. In this range, the risk of bleeding and thromboembolic complications is minimized, increasing the effectiveness and safety of the treatment. The inhibitors of vitamin K are the most common oral anticoagulants (OAC) in the clinical pratice and warfarin is the most used OAC in Brazil. Warfarin has a narrow therapeutic index and a wide variability in the dose response to the treatment Therefore, it requires periodic laboratory monitoring. The prothrombin time (PT) is the most common method used to monitor anticoagulant therapy through the International Normalized Ratio (INR). The INR ranges from 2.0 to 3.0 for most indications. This study aims to investigate the quality of oral anticoagulation in patients with heart disease, attended at two anticoagulation clinics (AC) linked to two university hospitals in the city of Belo Horizonte. This is an observational retrospective cohort study that evaluated sociodemographic and clinical variables. A total of 544 patients was evaluated, with a median age of 63.7 (Quartile 1 (Q1) 54.3, Quartile 3 (Q3) 73.6) years, the majority was female (57.4%), presenting a low degree of schooling and income. Atrial fibrillation (AF) was the most predominant OAC indication (77.1%). The median fraction of the INR in the therapeutic range was 53.5% (Q1 43.5, Q3 62.5) and the median of the TTR was 64.3% (Q1 54.0, Q3 74.0). The median of medications used including warfarin was 6.0 (Q1 5.0, Q3 7.0) and the majority of patients presented comorbidities (97.5%, median 3.0 (Q1 2.0, Q3 5.0)). The institutional TTR was considered satisfactory, mainly when it was obtained in a developing country and in a patient group with low socioeconomic and cultural level. However, low individual TTR was observed for 210 (38.4%) patients.